Development of a community-based social collaborative e-learning model for adaptability of higher education students in Indonesia - Purbasari, Imaniar; Yusuf, Munawir; Subagya,; Marmoah, Sri; Alali, Ahmad Alhussin (Frontiers in Education, 2025)
IntroductionThe rapid evolution of educational needs in the 21st century calls for innovative models that enhance students’ adaptability to dynamic socio-cultural and professional environments. This study aims to develop and evaluate the model’s effectiveness as a community-based social collaborative e-learning model designed to improve the cognitive, behavioral, and emotional adaptability of higher education students in Indonesia.MethodsThe study used a Research and Development (R&D) approach that involved three phases: needs analysis, model development, and testing. The study involved three phases: needs analysis, model development, and testing. The study involved 300 students, 45 males and 255 females, from three universities in Central Java, Indonesia. Data were collected through surveys, interviews, and pre- and post-intervention assessments. Quantitative data were analyzed using descriptive statistics and paired t-tests, while qualitative data were interpreted through thematic analysis.ResultsThe study results demonstrated a substantial increase in student adaptability by implementing the community-based social collaborative e-learning model, supported by technology as a key learning resource. This improvement was evidenced by a significant rise in the adaptability scores, with an average pre-intervention score of 41.92 and a post-intervention score of 48.87. Key factors influencing this adaptability enhancement included literacy skills, the ability to critically analyze phenomena, effective collaboration in social projects, strong social interaction skills, and problem-solving capabilities. These results underscore the model’s effectiveness in fostering critical competencies for dynamic and collaborative learning environments. However, limitations such as digital infrastructure disparities, the absence of adaptive mechanisms for diverse learning styles, and the need for long-term evaluation of adaptability improvements were identified.ConclusionThe community-based social collaborative e-learning model offers a robust framework for enhancing student adaptability in Indonesia’s higher education system. While the model demonstrates significant potential, addressing its limitations and expanding its scalability to varied educational contexts are necessary for maximizing its impact. This study provides a foundation for innovative educational practices that prepare students to thrive in dynamic, interconnected global and local landscapes.